Menstrual irregularity in women with acromegaly. - Kaltsas, G; Mukherjee, J; Jenkins, P; Satta, M; Islam, N; Monson, J; Besser, G; Grossman, A (1999)
Menstrual irregularity is common in women with acromegaly, occurring in 40-84%. Although it has been attributed to gonadotropin deficiency and/or PRL excess, it has not been evaluated in detail, and its pathogenesis is not well understood. To explore the various possible pathogenic mechanisms, we have analyzed the clinical, endocrinological, and radiological characteristics of 47 women with active acromegaly within the reproductive age range (15-41 yr) with respect to their menstrual pattern; 9 patients (19%) had normal cycles, 7 (15%) had oligomenorrhea, 29 (62%) had amenorrhea, and 2 (4%) had polymenorrhea. Compared to patients with normal cycles (n = 9), patients with menstrual irregularity (oligo/polymenorrhea or amenorrhea; n = 38) were more hirsute, had lower serum estradiol (normal: median, 76.5 pmol/L; range, 20-570; menstrual irregularity: median, 283; range, 140-431; P < 0.01), and sex hormone-binding globulin (SHBG; normal: median, 19.6 nmol/L; range, 5-52; menstrual irregularity: median, 48; range, 18-60; P < 0.01), but similar testosterone levels; in addition, patients with amenorrhea had higher serum GH (normal: median, 100 mU/L; range, 8.8-400; amenorrhea: median, 30; range, 10.7-120; P < 0.05). PRL levels in excess of 1000 mU/L were found in 16 of the 38 patients with menstrual irregularity compared to only 1 of the 9 patients with normal cycles. Patients with menstrual irregularity had a greater impairment of anterior pituitary function than patients with normal cycles. Acromegalic patients who were defined as estrogen sufficient (estradiol, >140 pmol/L) had clinical baseline endocrine profiles and LH responses to GnRH stimulation similar to those in patients with polycystic ovarian disease. There was a positive correlation between GH levels and tumor size (r = 0.35; P < 0.05) and an independent inverse correlation between GH and SHBG levels (r = -0.6; P < 0.01), which persisted even in patients who were estrogen sufficient, but there was no correlation between GH and estradiol levels; in addition, there was a negative correlation between estradiol levels and tumor size (r = -0.42; P < 0.05). Thirty-five of the patients with menstrual irregularity had meso- or macroadenomas and 3 had microadenoma, whereas 6 of the 9 patients with normal cycles had microadenomas. In conclusion, menstrual irregularity is common in women with acromegaly (81% of our patients). Amenorrheic patients have higher GH levels, are mainly estrogen deficient, and tend to have larger tumors than patients with normal cycles. However, the independent negative correlation between GH and SHBG levels suggests that GH may, directly or indirectly, lead to a fall in SHBG, possibly determined by the hyperinsulinemia known to occur in acromegaly. Low SHBG levels may contribute to the menstrual disturbance seen in acromegaly in addition to any gonadotropin deficiency or hyperprolactinemia and may account for hirsutism in the presence of normal testosterone levels.